О возможности иннервации ннтраоргапиыми нейронами гладкомышечных клеток в надпочечнике у некоторых животных - Богданова, М.И. (Вестник зоологии, 1977)
Topography and structure of adrenal glands neurons in dogs and cats were studied by the methods of Bil'shovskij-Gros, Kampos and Rasskazova. It is shown that the bulk of microganglia is localized near the capsule. Single neurons predominate in the organ thickness. Species peculiarities are detected in distribution of nerve cells in the animals under study. Intraorgan neurons are presented by afferent and efferent nerve cells of different structure. The functionnal significance of intraorgan neurons as peripheral centres of the organ activity regulation consists in receptor and effector innervation of the parenchyma, vascular wall and smooth mascular tissue of the adrenal glands.